2004
DOI: 10.1210/jc.2003-031037
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins Differentially Modulate Progesterone Receptor-A and -B Expression in Human Myometrial Cells: Evidence for Prostaglandin-Induced Functional Progesterone Withdrawl

Abstract: We tested the hypothesis that prostaglandin (PGs), PGE2, and PGF2 alpha, stimulate labor and delivery in women, in part, by inducing functional progesterone withdrawal in myometrial cells by increasing the progesterone receptor (PR)-A/PR-B expression ration. PHM1-31 cells (an immortal pregnant human myometrial cell line) were exposed to PGE2, PGF2 alpha, cyclic-8-bromoadenosine monophosphate (8-Br-cAMP) and phorbol 12-myristate 13-acetate (PMA) at various concentrations for 24h. Effects on PR-A and PR-B expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 0 publications
6
70
2
3
Order By: Relevance
“…NF-kB activity is observed during human labor. This mediates COX-2 expression and is involved in the ''functional'' progesterone withdrawal (35).…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB activity is observed during human labor. This mediates COX-2 expression and is involved in the ''functional'' progesterone withdrawal (35).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this phenomenon holds true in the regulation of PLA2G4A expression in human amnion fibroblasts is unknown. As have been reported that the functional progesterone withdrawal is facilitated by PGs via increasing the expression ratio of PGRA/PGRB in human myometrium (Madsen et al 2004), thus it is very likely that the expression of PGRA is under the control of glucocorticoids in this cell type since glucocorticoids are potent stimulators of PG synthesis in human amnion fibroblasts. To address the above issues, we investigated the effect of glucocorticoids on the expression of PGRA as well as the role of PGRA in the induction of PLA2G4A expression by glucocorticoids in human amnion fibroblasts.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, unlike in most of other species that progesterone withdrawal is achieved by a rapid fall in progesterone level prior to the onset of labor, the progesterone withdrawal in humans has been suggested to be achieved functionally via the expression of progesterone receptor A (PGRA) form under the influence of PGs in the myometrium (Allport et al 2001, Madsen et al 2004. PGRA is a N-terminal truncated form of the classical progesterone receptor B (PGRB) form, lacking 164 amino acids at the N-terminus compared to the fulllength PGRB (Graham & Clarke 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The diminished progesterone influence leads to an estrogen dominance (Mesiano et al 2002). Prostaglandins have been shown to induce an increased nPR-A/nPR-B ratio through the protein kinase C (PKC) pathway in human myometrial cells (Madsen et al 2004). Proinflammatory IL-1 up-regulates nPR-C in human myometrial cells, leading to diminished activation of nPR-B (Condon et al 2006).…”
Section: The Myometriummentioning
confidence: 99%
“…The increased expression of specific membrane-associated PRs (mPRs) at parturition augments contractility by decreasing intracellular cyclic adenosine monophosphate (cAMP) and altering intracellular Ca 2+ levels. (Pieber et al 2001, Mesiano et al 2002, Madsen et al 2004, Mesiano 2007.…”
Section: The Myometriummentioning
confidence: 99%